1997
DOI: 10.1177/108835769701200308
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Intake and Obesity in Children with Autism

Abstract: Many children with autism have idiosyncratic food preferences and eating habits that are difficult to regulate. The nutrient intake of 54 school-age Canadian children with autistic spectrum disorders, at mean age 13.3 years, was assessed using 3-day food consumption diaries compiled by parents or caregivers. The food records were analyzed for energy, minerals, vitamins, carbohydrates, protein, and fat content and compared with the recommended nutrient intake (RNI) for Canadians. All children had adequate prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 18 publications
3
70
1
Order By: Relevance
“…Our findings are similar to reports from other researchers [3,[13][14][15]. Edmond et al [3] reported adequate energy intake and growth in children with ASD, although their diets were less varied when compared to a group of control children.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are similar to reports from other researchers [3,[13][14][15]. Edmond et al [3] reported adequate energy intake and growth in children with ASD, although their diets were less varied when compared to a group of control children.…”
Section: Discussionsupporting
confidence: 92%
“…However, this latter explanation would be inconsistent with the robust differences we found between Notably, some variables had no association with unhealthy weight among children with ASDs. In contrast to previous studies, 70,74 there was no significant association between severity of ASD symptoms, and neither adaptive nor intellectual functioning was associated with overweight or obesity in multivariate models. In contrast to studies of typically developing children 75,76 but consistent with previous research in children with ASDs, 77 GI problems were not linked to overweight or obesity.…”
Section: Discussioncontrasting
confidence: 54%
“…Different dietary patterns (caused by the unusual feeding behaviours) and preference for specific foods can lead to the development of under or overweight as well as nutritional imbalances (i.e. inadequate or excess intake of nutrients) [13][14][15]18,20,25,71,72]. This study gathered some data on the foods that the adolescents particularly liked eating or refrained from, but the number of selective adolescents [24] was not sufficient to establish a statistical relationship between inadequate intakes and food selectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the current research proposes children with ASD may be at great risk or even greater risk for overweight and obesity in comparison to their typically developing (TD) peers [13][14][15][16][17][18][19][20]. The existing literature suggests that obesity is at least as high or higher in children with ASD than in TD ones [20][21][22].…”
Section: Introductionmentioning
confidence: 99%